PROFILE OF HIV/AIDS PATIENTS COINFECTED WITH TUBERCULOSIS IN IBNU SINA DISTRICT HOSPITAL, GRESIK,EAST JAVA, INDONESIA - Widyaningrum, Lilik N.; Indriati, Dwi W.; Diyantoro; Sundari, Aliyah Siti (Journal of Vocational Health Studies, 2022)
Background: HIV/AIDS cases continue to increase globally. A person with a weak immune system, especially people with HIV/AIDS, is very susceptible to various diseases, such as tuberculosis. Tuberculosis infection can be associated with HIV-positive individuals, which is caused by damage to cellular immunity due to the reduced number and function of CD4 cells. Purpose: To determine the profile of HIV/AIDS patients with TB coinfection based on CD4 values in RSUD Ibnu Sina Gresik. Method: The method used is observational analytical cross-sectional. Patients with TB and HIV coinfection were recapitulated from the Case Report Form (CRF). The results are presented in a frequency distribution table. Result: The study obtained information about 36 people with TB co-infected HIV/AIDS cases. Patients with CD4 values <200 cells/mm3 were 35 people (97.22%), and most of them were in the age group of 20-60 years were 35 people (97.22%). Male patients (83.33 %) dominate compared to female patients (16.67%). The duration of TB coinfection in HIV/AIDS patients occurs in less than one month, which is 21 people (58.33%). Conclusion: The profile of HIV/AIDS patients co-infected with TB is based on CD4 values that are more dominant in men, with the highest age being 20 - 60 years.